A large scale analysis of the dynamic cell behaviours that underlie the growth of the zebrafish porterior body - Duarte, Fernando António Vinagre, 1990- (2014)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2014